The Disappearance of the Other: A Note on the Distortion of Love - Engdahl, Emma (Qualitative Sociology Review, 2020)
Against the backdrop of contemporary sociological theories of love, this article explores the disappearance of the other in contemporary love relationships by focusing on the relationship between love and depression. The aim of the article is twofold: first, to provide a theoretical framework to be able to grasp in what ways the other is threatened with erosion in contemporary love relationships and why this may cause depression; second, to exemplify it with empirical data consisting of human documents such as novels, interviews, sms- and messenger-correspondence. The first section, excluding the introduction, consists of methodological reflections. The second section introduces Hegel’s thinking on love and discusses the perception of it by thinkers such as Honneth, Sartre, and Beauvoir, as well as its parallels with Giddens’s idea on confluent love as a new egalitarian paradigm for equality in intimate relationships. The third section is mainly devoted to Kristeva’s theory of the melancholic-depressive composite, but also introduces Illouz’s concept of autotelic desire. In the fourth section, Han’s idea of “the erosion of difference” and Bauman’s thinking on “the broken structure of desire” are discussed in relation to the use of Tinder in contemporary culture. The fifth section consists of an analysis of excerpts from contemporary love novels and interviews that illustrates the disappearance of the other in contemporary love relationships. In the sixth section, a number of longer passages from a messenger conversation, ranging over a couple of months in duration, is reproduced and interpreted, mainly by help of Kristeva’s thinking, in order to make visible the relation between the erosion of the other and melancholic depression. The article ends with a short conclusion.